Miniaturization of Ultra-wideband (UWB) band pass filter micro strip based on folded distributed method frequency 3.1 – 10.6 GHz - Aribowo, Didik; ., Herudin; Malik, Fitrah; Firmansyah, Teguh (International Journal of Engineering and Technology, 2018)
Filter plays a very important role in many application of RF/microwave/ultra-wideband technology. UWB is a technology which is interested for researcher since being published on February 14, 2002 by U.S Federal Communication Commission (FCC) which has been ap-proved including unlisence frequency at the range of 3.1 – 10.6 GHz and designated for commercial communication. As novelty, this re-search is proposed of miniaturization of ultra-wideband (UWB) bandpass filter microstrip based on folded distributed method frequency 3.1 – 10.6 GHz. This filter is a depiction of a microstrip substrate Duroid 5880 with relative its dielectric constant as 2.2 and its thickness as 0.787 mm. initial dimension of its filter can be calculated by using simulation software ADS 2011. The result of conventional filter de-sign is fa = 2.80 GHz, fb = 10.48 GHz, BW = 7.68 GHz fc = 6.346 GHz Fbw = 1.210 %. The result of outer folded filter design is fa = 3.475 GHz, fb = 9.650 GHz, bw = 6.175 GHz fc = 6.562 GHz fbw = 0.941 %. The result of inner folded filter design is fa = 3.400 GHz, fb = 9.925 GHz, bw = 6.525 GHz fc = 6.663 GHz fbw = 0.979 %. This result also shows that the usage of UWB outter folded filter has reduction the filter size of 4.25 % and for UWB inner folded filter size reduction of 42.85 % in term of filter size. Overall, these results indicate that filter has good performance with compact size.